Verbal autopsy of 48 000 adult deaths attributable to medical causes in Chennai (formerly Madras), India - Kanaka Santhanakrishnan; Peto Richard; Gajalakshmi Vendhan; Balasubramanian Sivagurunathan (BMC, 2002)
Abstract Background In the city of Chennai, India, registration of the fact of death is almost complete but the cause of death is often inadequately recorded on the death certificate. A special verbal autopsy (VA) study of 48 000 adult deaths in Chennai during 1995-97 was conducted to arrive at the probable underlying cause of death and to measure cause specific mortality rates for Chennai. Methods Trained non-medical graduates with at least 15 years of formal education interviewed the surviving family members or an associate of the deceased to write a report on the complaints, symptoms, signs, duration and treatment details of illness prior to death. Each report was reviewed centrally by two physicians independently. The reliability was assessed by comparing deaths attributed to cancer by VA with records in Vital Statistics Department and Chennai Cancer Registry. Results The VA reduced the proportion of deaths attributed to unspecified medical causes and unknown causes from 37% to 7% in early adult life and middle age (25-69 yrs) and has yielded fewer unspecified causes (only 10%) than the death certificate. The sensitivity of VA to identify cancer was 94% in the age group 25-69. Conclusion VA is practicable for deaths in early adult life or middle age and is of more limited value in old age. A systematic program of VA of a representative sample of deaths could assign broad causes not only to deaths in childhood (as has previously been established) but also to deaths in early adult life and middle age.